The Educational Supervisor’s Performance in Light of Applying the Knowledge Economy in the Education Directorates of Zarqa Governorate in the Hashemite Kingdom of Jordan - Alkhazaleh, Mohammad Salman Fayyad (CEPS journal, 2019)
This study aimed at identifying the performance of the educational supervisor in the light of applying the knowledge economy in the education directorates of the Zarqa Governorate, Jordan. For this purpose, the researchers constructed a study instrument with 35 items distributed over four areas: (educational planning, educational management, teachers’ professional growth, and curriculum building). Its validity and reliability were verified and later distributed to the study population, which consisted of 100 educational supervisors. The researchers utilised the descriptive method for its suitability to the study nature. The study found that the performance of the educational supervisor, in the light of applying the knowledge economy concept in the education directorates of the Zarqa Governorate, was medium. Furthermore, there were no statistically significant differences of the effect of the experience and directorate variables on all the study areas. Finally, the researchers made recommendations and suggestions relevant to the results.